Applicability of Standardized Physical Fitness Tests in Children with Different Types of Disabilities - (:unkn) unknown (INT JOURNAL SPECIAL EDUCATION, 2018)
Adapted fitness tests and tests for children without disabilities are used for evaluating the effects of physical training programs of children with disabilities. This study investigated the applicability of those frequently-used tests for children with different types of disability. A total of 282 children ages between 5 and 14 years with Cerebral Palsy, Spina Bifida, Brachlial Plexus Injury, Spinal Cord Injuries, Amputations, Neuromuscular Diseases, Traumatic Brain Injury, Orthopedic Deformity, Intellectual Disability, Down Syndrome were participated in the study. Gross Motor Function Measure, Modified Ashworth Scale, Posture Analysis, Berg Balance Scale, Sitting Balance, 9 Holed Peg, Sit and Reach, Pro-agility, Anticipation Time, Curl-up, Modified Curl-up, Lateral step-up, Hand grip, Medicine Ball Throw, Pull up and 6 Minute Walk tests were used for evaluation. The major result of this study is that the differences in physical fitness levels, functionality and severity of sequelae rule out using several tests commonly even if the type of disability is the same.
Keywords: assessment; evaluation; disability; adapted; MOTOR FUNCTION MEASURE; NEURAL-TUBE DEFECTS; CEREBRAL-PALSY; ASHWORTH SCALE; PREVALENCE; RELIABILITY; INTERRATER; SPASTICITY; TURKEY